2018
DOI: 10.1039/c7ra13069d
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Cu2ZnSn(S,Se)4photovoltaic devices with 10% efficiency by optimizing the annealing temperature of precursor films

Abstract: The annealing temperature of solution-processed Cu 2 ZnSn(S,Se) 4 (CZTSSe) precursor films has been carefully optimized for favorable selenization. At higher temperature, more solvent will be removed, and the crystallinity of the precursor films can be improved. It is found that, although the crystallinity of selenized film is continuously enhanced by increasing the temperature, a dense CZTSSe film with round and large grains can only be achieved at medium high temperature ranging from 350 to 400 C. Further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Using the sulfurized CZTS film, more than 10% of the efficiency were reported [25][26][27][28]; therefore, further research on applying the photo-sintering technique is required to replace the conventional thermal annealing process. Wu et al have demonstrated that the temperature of the annealing process for CZTS film can affect the efficiency of the solar cell [29]. By controlling the light intensity and dosage, a more optimized grain size can be achieved and this may lead to high efficiency of the photo-sintered CZTS solar cell device.…”
Section: Resultsmentioning
confidence: 99%
“…Using the sulfurized CZTS film, more than 10% of the efficiency were reported [25][26][27][28]; therefore, further research on applying the photo-sintering technique is required to replace the conventional thermal annealing process. Wu et al have demonstrated that the temperature of the annealing process for CZTS film can affect the efficiency of the solar cell [29]. By controlling the light intensity and dosage, a more optimized grain size can be achieved and this may lead to high efficiency of the photo-sintered CZTS solar cell device.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, many researches have focused on improving the quality of CZTSSe absorption layer, i.e., optimizing the synthesis method, adjusting element composition of CZTSSe precursor solution, or controlling the annealing conditions for sulfuration or selenization [9][10][11][12][13] . Recently, partial cation substitution of Cu + , Zn 2 + and Sn 4 + by Ag + , Cd 2 + and Ge 4 + has shown promising effect to boost the efficiency of kesterite solar cells [14][15][16][17][18][19][20] .…”
Section: Cu 2 Znsnsmentioning
confidence: 99%
“…However, this would hinder the grain growth and result in poor crystalline quality, which is undesired for high‐performance solar cells. [ 16 ] Higher temperature and longer annealing time are necessary to assist interdiffusion of elements, incorporate chalcogen element, and promote grain growth to obtain high crystalline film for high‐performance solar cells. [ 17 ] Therefore, it is important to develop a balanced annealing condition which can give highly crystalline CZTSSe thin films and preserve the back interface at the same time.…”
Section: Introductionmentioning
confidence: 99%